2021
DOI: 10.3389/fonc.2021.695770
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Co-Deletion of Type I Interferons and CDKN2A Genes in Thoracic Cancers: Potential Consequences for Therapy

Abstract: Homozygous deletion (HD) of the tumor suppressor gene CDKN2A is the most frequent genetic alteration in malignant pleural mesothelioma and is also frequent in non-small cell lung cancers. This HD is often accompanied by the HD of the type I interferons (IFN I) genes that are located closed to the CDKN2A gene on the p21.3 region of chromosome 9. IFN I genes encode sixteen cytokines (IFN-α, IFN-β…) that are implicated in cellular antiviral and antitumor defense and in the induction of the immune response. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…We found that HD of type I interferon ( IFN ‐ I ) genes was the most frequent type of copy‐number variation (CNV) accompanying CDKN2A and CDKN2B HD in LUAD. A previous report suggested that homozygous co‐deletion of IFN‐I and CDKN2A is a potential biomarker for therapy in thoracic cancers [ 16 ]. There are 16 IFN ‐ I genes located on chromosome 9p21 that share a common receptor, induce immune response, and participate in cell antiviral and anti‐tumor defense.…”
Section: Introductionmentioning
confidence: 99%
“…We found that HD of type I interferon ( IFN ‐ I ) genes was the most frequent type of copy‐number variation (CNV) accompanying CDKN2A and CDKN2B HD in LUAD. A previous report suggested that homozygous co‐deletion of IFN‐I and CDKN2A is a potential biomarker for therapy in thoracic cancers [ 16 ]. There are 16 IFN ‐ I genes located on chromosome 9p21 that share a common receptor, induce immune response, and participate in cell antiviral and anti‐tumor defense.…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2A is also a classical genomic alteration of mesothelioma (35). However, what is less known is the usual loss of type I interferon genes together with CDKN2A losses (37). Interestingly, those CDKN2A associated type I interferon losses have been shown to present altered immune gene signatures in tumors (38).…”
Section: Genomic Somatic Copy Number Alterations Correlate With Plasm...mentioning
confidence: 99%
“…Tumor cells with reduced IFN-I expression may evade immune cells due to a lack of IFN-α and - ß cross talk to the immune system. Loss or reduction of this central coordinator mechanism for the tumor–immune interaction would contribute to immune escape and ICI resistance ( Grard et al, 2021 ), especially in the context of tumor-targeted combination approaches.…”
Section: Genetic Features Of Pdac May Influence Immune Cell Functionmentioning
confidence: 99%